After the Honeymoon: The Uneasy Marriage of Human Rights and the Environment Under the European Convention on Human Rights and in UK Law Under the Human Rights Act 1998 - Morrow, Karen (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2013)
The European Convention for the Protection of Human Rights and Fundamental Freedoms (1950) (ECHR) regime has, in the absence of specific coverage of environmental rights, developed a “creative” approach in its jurisprudence in this area, pressing a variety of other rights, notably: Article 6 (the right to a fair hearing); Article 8 (the right to privacy and family life); and Article 1 to the First Protocol of the ECHR (the right to enjoyment of property) into service. This creativity has achieved much in according indirect protection to individuals in this regard, but has also placed additional pressure on the already congested Convention system. The entry into force of the Human Rights Act 1998 (HRA) made long-held rights under the ECHR directly accessible in domestic law in the United Kingdom. This naturally spawned a wave of litigation. One of the most prominently litigated areas concerned the pursuit of a variety of environment-based rights claims. In the intervening decade, the application of the ECHR to environmental claims in the UK courts has generated somewhat mixed results. This is in part a result of the “patchwork” approach that has developed toward environmental claims within the Convention regime itself, but it is also a product of the nature of the relationship between the ECHR and domestic law and the content and ethos of both regimes. This article will conclude by briefly considering the on-going role of the ECHR regime in environmental cases in light of subsequent developments in this area of law, notably under the Aarhus Convention.